The Influence of the Crisis on Changes in Personal Spending of Individuals: Remembering the Crisis and the Decisions on the Consumption of Future Income - Atelj, Marko; Mikulandra Volić, Ivona; Perkov, Josipa (Oeconomica Jadertina, 2017)
The impact of the crisis on the change and the characteristics of personal consumption in the Republic of Croatia is a subject of numerous studies. The emergence of the crisis is perceived as an unforeseen shock to the consumer leading to a research about the extent that this shock had on decisions related to personal consumption and spending of future incomes. The question that remains is how long does the memory of the crisis lasts and how much time after the end of the crisis or its decrease it continues to affect decisions regarding the spending of individuals. In this paper, through a survey of 521 respondents, a research was conducted investigating whether the shock caused by the Swiss franc’s exchange rate fluctuations is influencing current consumption or the spending of future income through the use of loans. Are individuals expecting a re-occurrence of significant exchange rate changes and interest rates and are they making decisions on spending future income in the light of these expectations? In order to examine how the shock caused by changes in the Swiss franc exchange rate affects opinions about loans a binary logistic regression was used. The results show that the natural logarithm of chance that an individual was affected by the shock relating to his attitude towards loans was positively associated with the shock experience (p